2017
DOI: 10.1002/jcu.22477
|View full text |Cite
|
Sign up to set email alerts
|

Sonographic evaluation of the fetal spine position and success rate of manual rotation of the fetus in occiput posterior position: A randomized controlled trial

Abstract: MRFO is a safe and useful procedure that should be performed in second-stage arrest in OPP. A better performance was observed when supported by the US knowledge of the spine position. © 2017 Wiley Periodicals, Inc. J Clin Ultrasound 45:472-476, 2017.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 18 publications
0
13
2
Order By: Relevance
“…No significant differences were found in the growth of the vertebrae between the male and female fetuses in this study. One previous study reported that female fetuses mature more rapidly than male fetuses 20 . This finding may be attributable to the small number of samples in that study or to the different imaging method used.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…No significant differences were found in the growth of the vertebrae between the male and female fetuses in this study. One previous study reported that female fetuses mature more rapidly than male fetuses 20 . This finding may be attributable to the small number of samples in that study or to the different imaging method used.…”
Section: Discussionmentioning
confidence: 77%
“…One previous study reported that female fetuses mature more rapidly than male fetuses. 20 This finding may be attributable to the small number of samples in that study or to the different imaging method used.…”
mentioning
confidence: 91%
“…Digital (manual) vaginal examination correctly detects OP position about 80% of the time. 42 Diagnosis of OP position via digital examination is made by identifying the fetal sagittal suture and fontanels and their location in relationship to maternal pelvis and is confirmed when the posterior fontanel is palpated toward the sacrum and the anterior fontanel toward the symphysis. 41 Transabdominal ultrasonographic examination of fetal head position during the second stage of labor is highly accurate.…”
Section: Occiput Posterior Positionmentioning
confidence: 99%
“…Although the use of ultrasound is not a routine standard of care, the use of bedside ultrasound to confirm the location of the fetal back may be a valuable tool in the hands of trained practitioners to confirm the fetal position. A 2017 RCT demonstrated the use of bedside ultrasound to confirm head orientation and spine location significantly increased successful rotation ( P ≤ .001) and spontaneous vaginal birth ( P = .01) 20 . Additional literature highlighted the increased accuracy of bedside ultrasound to detect asynclitism, poor flexion, and occiput transverse presentation, as well as use of the occipital‐spinal angle to predict the likelihood of spontaneous vaginal birth 19 .…”
Section: Management Considerationsmentioning
confidence: 99%